Feedforward-based decoupling control of air supply for vehicular fuel cell system: Methodology and experimental validation. (1st April 2023) - Zeng, Tao; Xiao, Long; Chen, Jinrui; Li, Yu; Yang, Yi; Huang, Shulong; Deng, Chenghao; Zhang, Caizhi
Graphical abstract: Highlights: Decoupling control of air supply mass flow and pressure for vehicular fuel cell system is studied. A feedforward control structure is adopted to enable emergency operation under sensor failure. Feedback compensation loop is designed based on diagonal matrix decoupling method. Bench and actual vehicle experiments are carried out to validate the control performance. Abstract: Insufficient and time-delayed air supply reduces the performance and durability of fuel cell system in vehicular application. Considering the strong coupling between mass flow and pressure, the air supply subsystem is a complex two-input-two-output control object. A decoupling control method based on feedforward structure is proposed to independently control the intake mass flow and pressure. Through look-up tables established based on experimental results of compressor speed and throttle angle versus mass flow and pressure, the proposed method is able to quickly provide feedforward-based control reference for actuators. The control error of feedforward part is further eliminated by feedback loops designed using diagonal matrix decoupling method, which compensates compressor speed and throttle angle in a coordinated manner. The proposed method has been comprehensively validated through bench and real-world experiments using a prototype fuel cell vehicle. The results show that the proposed method effectively reduces the interaction of the coupled loops, achieving higher accuracy and stability. Compared with the strategy without decoupling compensation in feedback loops, the relative error is controlled within [-1%, 1%] with smaller variance and less control effort. Besides, according to real-world vehicle experiments, the proposed method has better anti-disturbance performance to air speed turbulence under varying vehicle speed.